Analysis, identification and visualization of subgroups in genomics. Issue 3 (21st September 2020) - Völkel, Gunnar; Laban, Simon; Fürstberger, Axel; Kühlwein, Silke D; Ikonomi, Nensi; Hoffmann, Thomas K; Brunner, Cornelia; Neuberg, Donna S; Gaidzik, Verena; Döhner, Hartmut; Kraus, Johann M; Kestler, Hans A
Abstract: Motivation: Cancer is a complex and heterogeneous disease involving multiple somatic mutations that accumulate during its progression. In the past years, the wide availability of genomic data from patients' samples opened new perspectives in the analysis of gene mutations and alterations. Hence, visualizing and further identifying genes mutated in massive sets of patients are nowadays a critical task that sheds light on more personalized intervention approaches. Results: Here, we extensively review existing tools for visualization and analysis of alteration data. We compare different approaches to study mutual exclusivity and sample coverage in large-scale omics data. We complement our review with the standalone software AVAtar ('analysis and visualization of alteration data') that integrates diverse aspects known from different tools into a comprehensive platform. AVAtar supplements customizable alteration plots by a multi-objective evolutionary algorithm for subset identification and provides an innovative and user-friendly interface for the evaluation of concurrent solutions. A use case from personalized medicine demonstrates its unique features showing an application on vaccination target selection. Availability: AVAtar is available at: https://github.com/sysbio-bioinf/avatar Contact: hans.kestler@uni-ulm.de, phone: +49 (0) 731 500 24 500, fax: +49 (0) 731 500 24 502